MARGIN IN LUBNA’S YASSEEN NOVEL ''THE MAN OF MARGINALIZED MIRRORS'' - Dr. Hawra Aziz Alaiwi Alkaim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Margin represents one of the main pillars that have received the attention of modern literary criticism as it focuses on a social group suffering marginalization,. The present study is an attempt to shed light on a novel by Lubna Yasseen, whose title is The Man of Marginalized Mirrors. The syntactic analysis of the title of the novel denotes the existence of a margin that occupies the narrative space. This margin is the man. The focus in the present study is on the margin, its mechanisms of action, how it dominates the character, and how it makes the character view the world through another viewpoint and measure itself with a scale in which its relationship with the other is loosened, which obscures it due to the domination of the rejection factor from the angle of the self with the other, which results in a terrible fall of the character. The present study focuses on the theme of the body and the psychological factor as the focus that planted the act of marginalization in the fictional character.